Effect of potassium on yield and the rust incidence of soybean: Effect of potassium on yield and the rust incidence of soybean - S B MAHAJAN; D K KATHMALE (Journal of Oilseeds Research, 2020)
In soybean, soil application of muriate of potash (MOP) @ 40 kg/ha and foliar spray of sulphate of potash (SOP) @ 2% at pod development helped in realizing high seed yield and low rust severity.